2004
DOI: 10.1523/jneurosci.3001-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of theDrosophilaVesicular Glutamate Transporter Leads to Excess Glutamate Release and a Compensatory Decrease in Quantal Content

Abstract: Quantal size is a fundamental parameter controlling the strength of synaptic transmission. The transmitter content of synaptic vesicles is one mechanism that can affect the physiological response to the release of a single vesicle. At glutamatergic synapses, vesicular glutamate transporters (VGLUTs) are responsible for filling synaptic vesicles with glutamate. To investigate how VGLUT expression can regulate synaptic strength in vivo, we have identified the Drosophila vesicular glutamate transporter, which we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
390
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(418 citation statements)
references
References 43 publications
25
390
3
Order By: Relevance
“…Thus, either dDAB does not participate in dSYT1 sorting or sufficient redundancy is provided by interactions of SYT1 with at least two other CLATHRIN-associated adaptor proteins, AP-2 and Stonins (4,36). Furthermore, the distributions of other synaptic vesicle proteins at dab mutant synapses, including neuronal SYN-APTOBREVIN (38) and the vesicular glutamate transporter (39), were similar to those of WT (Fig. S6 K-T and U-D′, respectively).…”
Section: Discussionmentioning
confidence: 89%
“…Thus, either dDAB does not participate in dSYT1 sorting or sufficient redundancy is provided by interactions of SYT1 with at least two other CLATHRIN-associated adaptor proteins, AP-2 and Stonins (4,36). Furthermore, the distributions of other synaptic vesicle proteins at dab mutant synapses, including neuronal SYN-APTOBREVIN (38) and the vesicular glutamate transporter (39), were similar to those of WT (Fig. S6 K-T and U-D′, respectively).…”
Section: Discussionmentioning
confidence: 89%
“…Indeed, CSP, n-Syb, Syt I, and the Drosophila vesicular glutamate transporter (VGluT, Daniels et al, 2004) were respectively found to colocalize within these varicosities ( Fig. 6C-F).…”
Section: Synaptic Bouton-like Varicosities Also Form Within Axons Alomentioning
confidence: 92%
“…Following one hour incubation with a blocker solution (2-5% bovine serum albumin, 0.2% Tween-20 in PBS, PBT), the preparation was stained overnight at 4 ÂC using primary antisera, followed by one hour washes with PBT and 1-2 hours incubation with secondary antibodies at room temperature, and visualized using a Nikon fluorescence microscope. The following primary antibodies were used: rat anti-Syb (1:300, Wu et al, 1999), mAb anti-CSP (ab49, 1:20, Zinsmaier et al, 1994), rabbit anti-Syt (1:300, Mackler et al, 2002), mAb anti-Futsch (22C10, 1:100, Developmental Studies Hybridoma Bank), mAb anti-Hiw (6H4, 1:3, Wan et al, 2000), rabbit anti-DAP 160 (1:300, Roos and Kelly, 1999), mAb nc82 (1:20; Wagh et al, 2005), a polyclonal antibody to clathrin heavy chain (1:50) and to LAP (1:200, Zhang et al, 1998), a polyclonal antibody to glutamate receptor III (Marrus et al, 2004), a polyclonal antibody to the Drosophila vesicular glutamate transporter (VGluT, 1:500, Daniels et al, 2004), and a polyclonal antibody to HRP (Jan and Jan, 1982). Fluorescence-conjugated secondary antibodies were used 1:100 (Jackson Immunology Labs).…”
Section: Immunocytochemistry and Microscopymentioning
confidence: 99%
“…Bouin's fixative was used for vGLUT immunostaining, as reported by Daniels et al (2004). After permeabilization with 0.1% Triton X-100/PBS, preparations were incubated with primary antibodies at 4°C overnight.…”
Section: Immunocytochemistrymentioning
confidence: 99%